A new perennial species of Gomphrena (Amaranthaceae) from Mexico with nomenclatural notes on G. decumbens - Sandoval-Ortega, Manuel Higinio; Rodríguez-Pérez, Emmeth Josafath; Zumaya-Mendoza, Silvia (Phytotaxa, 2025)
Gomphrena caxcana (Amaranthaceae), a new species from the states of Jalisco and Zacatecas (Mexico), is described. It is morphologically similar to G. serrata, but it can be distinguished by the fleshy perennial taproot (vs. fibrous usually annual root), the presence of adventitious roots at the base of the stems (vs. absence of adventitious roots), the length of bractlets (3–4 mm vs. 4.8–7.4 mm), and the structure of staminal tube (with two short apical lobules between anthers vs. a single apical lobule between anthers). The name Gomphrena decumbens is also discussed and lectotypified.